Malpractice in Psychiatry - Aydoğdu, Halil İlhan (The Bulletin of Legal Medicine, 2023)
Medical malpractice is defined as the harm caused by the physician or health personnel not performing the standard practice in the diagnosis and treatment process, lack of skills or not giving treatment. What is emphasized in the definition as “not making the standard practice in the diagnosis and treatment process” is actually a long process. The diagnosis and treatment process, which starts with inspection since the patient-physician relationship is established, sometimes continues with operations for surgical branches and sometimes requires the establishment of a long-term follow-up relationship. Errors caused by negligence, carelessness or lack of knowledge that can be made at any point in this process result in medical malpractice. Psychiatry is one of the departments that can be considered low risk in terms of malpractice. Some of the malpractices in psychiatry can actually be seen in any part of the medical field in general. This group includes deficiencies in information and consent, deficiencies in examination and diagnostic errors, incorrect medication administration, and errors in the management of complications. In addition to these, wrong/incomplete treatment in the patient in the second group with a suicidal idea plan-attempt and conditions such as wrong/incomplete treatment in the patient who has a tendency to harm himself or his environment, violation of personal boundaries (sexual and non-sexual), wrong compulsory hospitalization decisions, violation of the principle of secrecy and stigma are highly specific to psychiatry. Psychiatry is a branch that should be evaluated specifically in terms of medical malpractices due to its unique characteristics.